Design and optimization of ultrasonic array transducers for medical imaging applications - Wang, Qiong Bo (2008)
This thesis investigates the properties of ultrasonic array transducers based on broadband analysis, in particular their radiation fields. And furthermore, the methods to design and optimize broadband sparse arrays are developed for both 1D and 2D arrays, which can be used to satisfy different application requirements.